Higiene Dan Sanitasi Kantin Sekolah Dasar - Aliefiyah Na'imatul Azizah; Merrisa Ayu Oktanova (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2018)
Abstract: Hygiene and Sanitation of Primary School Canteen. Snacks food in the canteen become school children's needs of additional intake while in school. Snacks food become routinely consumed by school children’s because it is one of the providers of food in the school environment. School canteen in providing snacks food should be able to pay attention to hygiene and sanitation. Hygiene and food sanitation play an important role because if the hygiene and sanitation of food in bad processing then it can lead to disease. The purpose of this research is to know the hygiene and sanitation of 22 primary school canteens in the working area of Puskesmas Mojopanggung in 2018. The method used in this research is descriptive and research design is observational. There are 5 variables that become the assessment in this research that is location; building; and environmental hygiene, sanitation facilities, personal hygiene of food handlers or sellers, food security, and health promotion tools. The result of assessment of location, building and environmental cleanliness variables is 74,75%, sanitation facility variable equal to 65,4%, personal hygiene variable food handler or seller equal to 73,5%, food security variable equal to 77,8%, and means of health promotion by 60%. Category of health promotion means to be one category that does not meet the requirements, while the other four variables get the medium category. In general, 5 variables in the hygiene and sanitation of 22 primary school canteens in Puskesmas Mojopanggung in 2018 were medium category with percentage of 70.29%.